R-Vivaldi:distance range-aware IP network coordinate system - Da-bin WANG; Qiong HUANG; Xiao-long YANG; Ke-ping LONG (Tongxin xuebao)
The experience showed that the predicted delay's accuracy was improved when the nodes were chosen around the given delay as anchors.Thus a distance range-aware IP network coordinate system(R-Vivaldi) was proposed.The main idea was:according to the approximate range of the predicted delay,the anchors were re-selected in the radius area of the approximate range to compute the new range.In accordance with the above process,the coordinate system constantly iterated the network distance and dynamically chose anchors until the prediction accuracy meet the requirement.Experiments show that the approach can not only effectively improve the prediction accuracy of delay but also overcome inconsistencies of the prediction accuracy to a certain extent.